PENEMPATAN TENAGA KERJA LOKAL DALAM EKPLOITASI TIMAH DI PULAU TOPANG KABUPATEN KEPULAUAN MERANTI - ", M. Haryadi; Yusri, Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is motivated because not optimal placement of local labor in PT. Perkit Wahana Jaya, still more use of labor from outside the area in the Company Tin Perkit Wahana J aya. Based on this background, this research aims at (i) To determine the government's role in local employment in PT. Perkit Wahana Jaya (ii) To determine the obstacles experienced by Meranti Islands regency government.This research is a descriptive study that aimed to describe the real situation on the ground to systematically and accurately related facts and research analysis unit, as well as field observations based on data (information) specific. Methods of data collection is done with interviews and document study. Government involvement is affected by competent human resources, strengthening related institutions as well as the availability of facilities and infrastructure financing as well. However, the implementation of the government will not succeed in the absence of community participation in supporting the program.The results showed that the government's role in local employment in the Company Tin Perkit Wahana Jaya ie government issued regulation No. 23 of 2011 concerning local employment and to super viseemployees.Keywords: Placement, the local Labor, Exploitation